Reflection of Suffering in the Context of the Covid-19 Pandemic for Believers Based on Jeremiah 29:11 - Djone Georges Nicolas (Budapest International Research and Critics University, 2022)
This study aims to reflect on suffering in the context of the Covid-19 Pandemic for believers based on Jeremiah 29:11 by choosing to use a descriptive qualitative method approach and literature analysis, collecting data through book sources including the Bible, some journals and various digital articles, as well as documents. They are related to the topic under study. The crisis of the Covid-19 pandemic has resulted in great anxiety, doubt, despair, depression and even death among all people, including believers. The presence of a pandemic that never ends is a reality and a threat that must be faced every day by everyone without exception. The result: First, believers must remain with all their heart, soul and body, trusting God's design and faithfulness in any condition, including in the process of suffering, because they believe God is sovereign over His plan. Second, believers must remain aware that God's purpose is related to the salvation of His people, so believers need and must view suffering from God's point of view.